(untitled) (Bangladesh Journal of Medical Science, 2025)
Mouthwashes have been extensively studied through clinical trials to assess their efficacy in improving oral health. This bibliometric analysis explores research trends, key contributors, collaborative networks, and thematic evolution in this field. The online search was performed in the PubMed database on August 29, 2024, using relevant keyword- string to identify relevant publications. After applying inclusion and exclusion criteria, 1,883 articles published between 1967 and 2024 were selected and analyzed using the bibliometric software VOSviewer and Biblioshiny. The coauthorship analysis identified several key collaborators: Addy M has the highest total link strength (TLS) value of 112. The Journal of Clinical Periodontology emerged as a leading journal, publishing 220 clinical trials on mouthwashes. The USA dominated the research output, followed by Brazil and India. In addition, Brazil showed the highest levels of international collaboration. The thematic analysis suggests that the focus of mouthwash clinical trials shifted from examining basic antibacterial efficacy and formulation to exploring personalized, long-term health effects and incorporating mouthwash into broader oral health and wellness strategies, including psychological aspects. The analysis also revealed that international partnerships are still limited while the field is highly collaborative, with only 5.79% of studies involving cross-border cooperation. This highlights potential areas for growth in advancing global research collaborations. The analysis also suggests that the field has evolved substantially. However, some areas are still underexplored, such as studies on the environmental impact of chronic mouthwash use and its effects on the natural balance of mouth bacteria, which warrant more attention. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 17-32